Inhibition of HER2 signaling and breast cancer cell growth with a novel antibody targeting HER2 ECD III/IV - Chunchun Liu; Yulei Ren; Xuan Luo; Peiyun Zhou; Xiangjuan Du; Qianmin Wang; Xue Han; Yanhui Xu; Ping Wang; Dan Zhao; Huirong Yang (PLoS ONE, 2026)
Human epidermal growth factor receptor 2 (HER2), a ligand-independent tyrosine kinase receptor belonging to the EGFR family, serves as a key oncogenic driver in breast, gastric, and several other solid tumors. Although anti-HER2 therapies have substantially improved survival outcomes—particularly in breast and gastric cancers—treatment resistance and cancer recurrence remain major clinical challenges. Thus, developing novel antibodies exhibiting complementary effects to the current anti-HER2 therapies could provide additional therapeutic benefits. Here, we describe two novel HER2-targeting monoclonal antibodies, m66 (murine-derived) and r40 (rabbit-derived), which inhibit breast cancer cell proliferation in vitro . Of the two, antibody r40 exhibits stronger suppression of the PI3K/AKT and MAPK signaling pathways compared to m66. Moreover, the addition of r40 to the combination of trastuzumab and pertuzumab leads to a significantly enhanced inhibitory effect. We also determined the cryo-EM structures of the HER2-m66-trastuzumab ternary complex and the HER2-r40-trastuzumab-pertuzumab tetrameric complex, at overall resolutions of 3.2 Å and 3.1 Å, respectively. Structural analyses reveal that m66 recognizes an epitope overlapping with that of pertuzumab, whereas r40 binds within the HER2 ECD III/IV—a region distinct from the binding sites of both trastuzumab and pertuzumab. These findings identify r40 as a promising therapeutic candidate for use in combination with trastuzumab and pertuzumab in the treatment of HER2-positive breast cancer.